2011
DOI: 10.1126/scisignal.2001309
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory ITAM Signaling Traps Activating Receptors with the Phosphatase SHP-1 to Form Polarized “Inhibisome” Clusters

Abstract: The ability of immunoreceptor tyrosine-based activation motif (ITAM)-bearing receptors to inhibit, rather than activate, signaling by other receptors is a regulatory mechanism of immune homeostasis. However, it remains unclear how inhibitory ITAM (ITAMi) receptor signaling and Src homology 2 (SH2) domain-containing phosphatase-1 (SHP-1), which is recruited to ITAMs, target multiple heterologous activating responses without coaggregating with the associated activating receptors. We found that ITAMi signaling tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 72 publications
4
67
0
2
Order By: Relevance
“…It is therefore interesting that a recent publication demonstrated strong recruitment and colocalization of IFN-g receptors with FcgRI upon stimulation with IC in a manner independent of IFN-g (34). Taken with our previous results, we hypothesize that the inhibition of IFN-g receptor signaling by high-avidity ligation of FcgRI may occur by a similar proximity-based mechanism as the monomeric ligation of FcaRI, as it shares the involvement of SHP-1 and the common g-chain (18), as well as SRC and SYK kinases (33). Interestingly, however, treatment of human monocytes with monomeric IgG has no such suppressive effect on IFN-g-dependent outcomes; although FcgRI has been shown to be normally occupied by monomeric IgG, eliciting a tonic signal to keep its inflammatory threshold in check (32), the mechanism for the more potent inhibitory signal evoked by high-avidity IC binding is most likely molecularly distinct.…”
Section: Discussionsupporting
confidence: 64%
“…It is therefore interesting that a recent publication demonstrated strong recruitment and colocalization of IFN-g receptors with FcgRI upon stimulation with IC in a manner independent of IFN-g (34). Taken with our previous results, we hypothesize that the inhibition of IFN-g receptor signaling by high-avidity ligation of FcgRI may occur by a similar proximity-based mechanism as the monomeric ligation of FcaRI, as it shares the involvement of SHP-1 and the common g-chain (18), as well as SRC and SYK kinases (33). Interestingly, however, treatment of human monocytes with monomeric IgG has no such suppressive effect on IFN-g-dependent outcomes; although FcgRI has been shown to be normally occupied by monomeric IgG, eliciting a tonic signal to keep its inflammatory threshold in check (32), the mechanism for the more potent inhibitory signal evoked by high-avidity IC binding is most likely molecularly distinct.…”
Section: Discussionsupporting
confidence: 64%
“…We confirmed these results using F(ab′) 2 fragments of anti-hFcγRIIA mAb IV.3 (Supplemental Figure 2, C and D). This was associated with the inhibition of ROS production induced by N-formyl-methionine-leucine-phenylalanine (fMLF) from hFcγRIIA (23). Recently, we demonstrated that hFcγRIIIA (CD16A), which is also associated with the common FcRγ subunit, was similarly able to induce ITAMi signaling following interaction with hIgG1, i.v.…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies revealed that the ligand valence determines the outcome of FcaRI-mediated cellular responses, whereby monovalent receptor targeting by anti-FcaRI Fab has an inhibitory effect, as opposed to polyvalent targeting that results in cellular activation (19,36,37). Therefore, we compared the effects of monovalent antiFcaRI Fab with polyvalent FcaRI targeting on neutrophil viability…”
Section: Differential Susceptibility Of Primed and Resting Neutrophilmentioning
confidence: 99%